‘Like the worst toothache you’ve had’ – How people with rheumatoid arthritis describe and manage pain - Bergström, M.; Ahlstrand, I.; Thyberg, I.; Falkmer, Torbjorn; Börsbo, B.; Björk, M. (Informa Healthcare, 2017)
Rheumatoid arthritis (RA) is a chronic inflammatory disease often associated with disability. Despite new treatments, pain and activity limitations are still present. Objectives: To describe how persons with RA experience and manage pain in their daily life. Methods: Seven semi-structured focus groups (FGs) were conducted and analyzed using content analysis. Results: The analysis revealed four categories: 1) Pain expresses itself in different ways referred to pain as overwhelming, aching or as a feeling of stiffness. 2) Mitigating pain referred to the use of heat, cold, medications and activities as distractions from the pain. 3) Adapting to pain referred to strategies employed as coping mechanisms for the pain, e.g. planning and adjustment of daily activities, and use of assistive devices. 4) Pain in a social context referred to the participants’ social environment as being both supportive and uncomprehending, the latter causing patients to hide their pain. Conclusions: Pain in RA is experienced in different ways. This emphasizes the multi-professional team to address this spectrum of experiences and to find pain management directed to the individual experience that also include the person’s social environment.